Kissing Bug ( spp.) Intrusion into Homes: Troublesome Bites and Domiciliation - Stephen A. Klotz; F. Mazda Shirazi; Keith Boesen; Norman L. Beatty; Patricia L. Dorn; Shannon Smith; Justin O. Schmidt (SAGE Publishing, 2016)
Kissing bugs ( Triatoma spp.) frequently enter homes and bite human and pet occupants. Bites may lead to severe allergic reactions and, in some cases, death. Kissing bugs are also vectors of Trypanosoma cruzi , the cause of Chagas disease. In general, modern houses in the United States are not conducive to domiciliation of kissing bugs (bugs living out their entire life within the home with the presence of eggs, nymphs, adults, and exuviae). Construction features such as concrete foundations, solid walls and ceilings, window screens, tight thresholds for doors and windows, and other measures impede bug entry into homes, and air conditioning reduces the need for open doors and windows. Where Chagas disease is endemic in Mexico and Central and South America, homes often have thatch roofs, adobe walls, and open doors and windows. We investigated numerous instances of kissing bug intrusions into homes in Southern Arizona, California, and Louisiana and documented the reactions to kissing bug bites. Our work confirms the importance of modern home construction in limiting kissing bug intrusions. Older homes, especially those lacking modern screening, caulking, and weather stripping to reduce air leakage, may be subject to kissing bug intrusions and domiciliation. We describe a community in Southern Arizona where domiciliation of homes by Triatoma recurva is common. We also provide recent data regarding kissing bug bites and allergic reactions to the bites.